Social Barriers to Physical Activity for Individuals with Physical Disabilities - Cappe, Shauna (Université d'Ottawa / University of Ottawa, 2012)
The purpose of this thesis was to explore socially constructed discursive barriers to physical activity for people with physical disabilities. This research was informed by a critical disability studies framework. Eight interviews were conducted, split between end-users and stakeholders. The end-user article discusses their perspectives with regard to their own PA participation, their use of PA resources, and their views of how disability is constructed. The stakeholder article deals with their views with regard to Canada’s progress in creating inclusive PA guidelines, the research process as it effects people with physical disabilities, and how disability is constructed. The results showed awareness among both groups of the social model of disability, but that the medical model is still firmly rooted. Work is needed to create inclusive promotional materials and disseminate them effectively. An effective advocacy and lobbying effort was suggested as one avenue towards a possible solution to this issue.
Keywords: Physical Disability; Health Promotion; Discourse; Medical Model; Social Model; Critical Disability Studies; Stakeholders; End-Users